STUDI TENTANG KEMAMPUAN MAHASISWA SEMESTER KE-4 PROGRAM STUDI BAHASA INGGRIS FKIP UNIVERSITAS RIAU DALAM MENGGUNAKAN PERSESUAIAN/KONKORD - Kurniatin, Wiwik; ', Syafri K; ', Erni (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This study was aimed to find out the ability of the fourth semester students of English Study Program of FKIP University of Riau in using agreements. The researcher used cluster random sampling technique to determine the sample. The samples were 26 students. The study was used to find out the ability in five types of agreements such as agreements with indefinite pronoun, agreements with expression of quantity, agreements with some irregularities, agreements with nouns with no singular form, and agreements with collective noun. Cloze procedure test was used to gain the data with the number of tests is 40 questions. The result of the study revealed that the total mean score was 56 which indicated students were in average level of ability. The highest score with the mean score 67.7 was in using agreements with nouns with no singular form, it is in good level. Whereas, the lowest score with the mean score 45.6 was in using agreements with collective noun, it is in poor level.Keywords: Students’ ability, Grammar, Agreements